Intestinal Obstruction- Etiological and Treatment Outcome - Atif Sharif, Tasleem Akhtar, Naeem Zia (Journal of Rawalpindi Medical College, 2015)
Background: To study the causes of intestinal obstruction with regards to symptoms,duration of symptoms and subsequent management. Methods: This observational study included 120 consecutive patients with clinical symptoms and signs of intestinal obstruction along with abdominal radiographic findings consistent with mechanical intestinal obstruction or those verified at operation subsequently to have obstructive pattern of disease. Immediate fluid and electrolyte resuscitation was started on every patient. Failure of relief of obstruction on this conservative treatment for more than 48-72 hours or development of signs of toxicity lead to exploratory laparotomy of the patient. Patients with clinical suspicion and previous history of tuberculosis were also initially kept on conservative regime and patients with failure of relief in 72 hours or clinical deterioration were subjected to laparotomy. Results: Abdominal tuberculosis(26.7%), adhesion(25%), obstructed hernias(12.5%), left sided malignancies(8.3%), volvulus(6.7%) , phytobezoar(6.7%), mesenteric ischemia(4.2%), worm infestation(4.2%), intussusceptions(1%) and colonic pseudo obstruction(1%) were the causes encountered in descending order. Chief complaints were abdominal distension(84%), vomiting(66%), absolute constipation(76%) and pain abdomen(70%). Majority (68.8%) of tuberculous patients underwent surgery and 67% of adhesion obstructions settled with conservative management. All the rest underwent surgery for the relief of symptoms. Conclusion: Intestinal tuberculosis is the main cause of intestinal obstruction in developing countries.